(untitled) (Al-Aasar, 2025)
Natural disasters, hardships, and various diseases in this world can be understood as trials, punishments, or consequences of disobedience to Allah. These occurrences are considered a test or retribution from Allah. This article adopts a research-based approach to examine the phenomenon. According to Islamic teachings, such events result from human corruption on earth, whereas science attributes them to atmospheric changes and underground movements. These disasters lead to significant loss of life and property. In such situations, three groups of people have specific responsibilities. Government authorities: implementing precautionary measures. Scholars: advising people to refrain from disobedience to Allah. General public: practicing patience, repentance, and seeking forgiveness.